Predictive value of renal shear wave elastography in liver cirrhosis: liver, pancreas and biliary tract - Hagel, Christian; Hirth, Michael; Bißbort, Jan; Teufel, Andreas; Hetjens, Svetlana; Ebert, Matthias; Antoni, Christoph Helmer (Digestive and liver disease, 2025)
Background - In liver cirrhosis, prognosis is profoundly affected by renal function. This study evaluates the usefulness of renal stiffness measurement by point-shear wave elastography and renal perfusion by duplex. - Methods - In this case-control study, organ stiffness was quantified using point-shear wave elastography and duplex sonography to calculate the arterial resistive (RI) and pulsatility indices (PI) in 123 patients, including patients with liver cirrhosis with (LC+A) and without ascites (LC-A) and patients without liver cirrhosis (NLC). - Results - PI and RI were significantly increased in LC-A and LC+A compared to NLC (p<0.001) and correlated with MELD and Child Pugh scores. Point-shear wave elastography showed significantly lower renal stiffness in LC+A compared to LC-A (p<0.01) and NLC (p<0.001). Renal stiffness correlated inversely with MELD and Child Pugh scores. Reduced renal stiffness, but not PI or RI, was associated with the presence of hepatorenal syndrome (p<0.001). Reduced renal stiffness was associated with an increased risk of death due to complications of liver cirrhosis within 3 years (p<0.01). - Conclusion - Point-shear wave elastography and duplex sonography correlate with progression of liver cirrhosis, but only shear wave elastography represents a valuable prognostic tool for hepatorenal syndrome and mortality in patients with liver cirrhosis.
Online verfügbar: 28. Oktober 2024, Artikelversion: 24. Januar 2025
Gesehen am 10.07.2025